2018
DOI: 10.1111/ceo.13442
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of scleral transillumination techniques to identify infant ciliary body for sclerostomy and intravitreal injections

Abstract: Importance There is variation in the literature for sclerotomy and intravitreal injection placement in young children, ranging from 0.5 to 3.0 mm from the limbus. We assess the accuracy of scleral transillumination to identify the ciliary body in infants for safe sclerotomy and intravitreal injections in young children. Background The study compares the perilimbal “dark band” seen on scleral transillumination (STI) with the ultrasound biomicroscopy (UBM), and compares these measurements with the current guidel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Neoplastic and uveitic applications (retinoblastoma and toxocariasis, respectively) are the most prominent posterior segment applications of UBM. Additional publications utilizing UBM to evaluate the pediatric posterior segment included correlation of scleral transillumination to UBM images for localization of intravitreal injection or sclerotomy site [77] and evaluation for choroidal detachment in the setting of rhegmatogenous retinal detachment [78].…”
Section: Corneamentioning
confidence: 99%
“…Neoplastic and uveitic applications (retinoblastoma and toxocariasis, respectively) are the most prominent posterior segment applications of UBM. Additional publications utilizing UBM to evaluate the pediatric posterior segment included correlation of scleral transillumination to UBM images for localization of intravitreal injection or sclerotomy site [77] and evaluation for choroidal detachment in the setting of rhegmatogenous retinal detachment [78].…”
Section: Corneamentioning
confidence: 99%
“…Further modifications developed by Lemley et al based on clinical experience suggested a slightly more posterior approach. Sharma et al, using STI as reported in this issue, identified similar dimensions to Lemley et al The advantage with the Sharma technique is the direct simplified clinical measurement technique independent of growth tables.…”
Section: Surgical Access To the Posterior Segmentmentioning
confidence: 99%
“…The recommended location for posterior segment sclerostomy placement varies widely in the literature depending on the method used to assess the location for different ages of the child . In this issue, Sharma et al describes a novel technique using scleral transillumination (STI) to accurately identify the ciliary body as the midpoint of the dark band on transillumination. In their study, there was good correlation between the ciliary body identified on ultrasound biomicroscopy (UBM) and STI in all cases.…”
mentioning
confidence: 99%
“…Intravitreal injections are applied through the pars plana of the CB, 3.5–4.0 mm posterior to the limbus [ 3 ]. For children, a distance of 0.5–3.5 mm from the limbus depending on the age is used [ 4 , 5 ]. For this reason, it is important to have a thorough anatomical understanding of the CB and its extent.…”
Section: Introductionmentioning
confidence: 99%